2016
DOI: 10.15376/biores.11.1.2349-2360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermo-Vacuum Treatment on the Color and Chemistry of Larch Wood

Abstract: The objective of this study was to investigate the color and chemical changes of thermo-vacuum treated larch wood. Specimens were heat treated in a vacuum at various temperatures for 4 h. The color parameters of untreated and heat-treated samples were measured using the CIELab color system. Changes in the chemistry of larch wood were investigated using X-ray photoelectron spectroscopy (XPS), electron spin resonance (ESR) spectroscopy, and UV-Vis spectroscopy. The results showed that the color of larch wood bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In recent years, the thermo-vacuum modification of wood has been developed as a new method to decrease the effects of oxygen on the loss of mechanical properties during heat treatment [18,19]. It has been found that the thermo-vacuum modification can also improve the dimensional stability of wood [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the thermo-vacuum modification of wood has been developed as a new method to decrease the effects of oxygen on the loss of mechanical properties during heat treatment [18,19]. It has been found that the thermo-vacuum modification can also improve the dimensional stability of wood [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the surface color of the compacts became darker with the increase of the forming pressure. The changes may also be due to the continuous thermal degradation of chemical components in the compacts with the increase of the holding time (Wang et al 2016).…”
Section: Effect Of the Holding Time On Color Changes Of The Compactsmentioning
confidence: 99%
“…The reason for the strength decline after 140 ℃ may be the mechanical strength reduction caused by the destruction of hemicellulose chain. Nevertheless, the fibers were eventually carbonized and the strength was reduced at higher temperature (Wang et al 2016).…”
Section: Mechanical Properties In Warm Compactionmentioning
confidence: 99%